Assistive device using computer vision and image processing for visually impaired; review and current status. (3rd April 2022) - Patel, Karan; Parmar, Bhavesh
Abstract: Purpose: The purpose of this article is to review the vision substitution devices based on computer vision and Image processing. The focus of this article is on reviewing devices that require coding and sensors mechanism. Methods: Review of existing and commercially available vision assistive devices has been done. Comparison is based on feedback mechanics, adaptability in the surrounding environment, and functionality of devices. The study extended to advanced researches based on computer science and image processing. The integration of object detection and face recognition techniques in assistive devices for visually impaired in specific applications has been studied. Comparative analyses were presented. Results: The findings from this study suggest that a few assistive devices are available commercially. The commercially available assistive devices influenced by the mindsets of visually impaired and economical benefits. A combination of several devices can be fruitful in eliminating the limitation of an available device. Ample researches have been done for navigation, communication, object detection, and object recognition to assist visual impaired. The primary results might be promising, but most studies are not tested in actual conditions. Conclusion: Various assistive devices for visually impaired are available commercially and several studies indicate further advancement. However, adaptability and trustworthiness are major issues. The primary reason behind this is the low-performance level of the device, feedback, and testing. The secondary reason is commercial availability and poor knowledge of the end-user. IMPLICATIONS FOR REHABILITATION: Advancement in computer science and image processing has paved the way to assist sensory impaired in doing various activities. Assistive technologies play a pivotal role in daily activities of visually impaired by assisting them for communication, and mobility. Assistive technologies can lead visually impaired to make them self-sustained. Very few research and devices related to assistive technology had reached the stage of testing and commercialization. Researchers can utilize the study in providing better assistive technology for the visually impaired.